Erythropoietin preserves the endothelial differentiation capacity of cardiac progenitor cells and reduces heart failure during anticancer therapies - Hoch, Melanie; Fischer, Philipp; Stapel, Britta; Missol-Kolka, Ewa; Sekkali, Belaid; Scherr, Michaela; Favret, Fabrice; Braun, Thomas; Eder, Matthias; Schuster-Gossler, Karin; Gossler, Achim; Hilfiker, Andres; et al. (Cell stem cell, 2011)
Anticancer therapies, such as targeting of STAT3 or the use of anthracyclins (doxorubicin), can induce cardiomyopathy. In mice prone to developing heart failure as a result of reduced cardiac STAT3 expression (cardiomyocyte-restricted deficiency of STAT3) or treatment with doxorubicin, we observed impaired endothelial differentiation capacity of Sca-1(+) cardiac progenitor cells (CPCs) in conjunction with attenuated CCL2/CCR2 activation. Mice in both models also displayed reduced erythropoietin (EPO) levels in the cardiac microenvironment. EPO binds to CPCs and seems to be responsible for maintaining an active CCL2/CCR2 system. Supplementation with the EPO derivative CERA in a hematocrit-inactive low dose was sufficient to upregulate CCL2, restore endothelial differentiation of CPCs, and preserve the cardiac microvasculature and cardiac function in both mouse models. Thus, low-dose EPO treatment could potentially be exploited as a therapeutic strategy to reduce the risk of heart failure in certain treatment regimens.